CULTURAL SIGNIFICANCE OF HAKKI PIKKI COMMUNITY TRADITIONS AND BELIEFS WITH SPECIAL REFERENCE TO HASSAN DISTRICT- A SOCIOLOGICAL APPROACH - K. S., Mohan Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper discusses the cultural significance of Hakki Pikki community traditions and beliefs with reference to Hakki Pikki community of Hassan district. Originally the Hakki Pikki community is a nomadic tribe of people moving in groups from place to place in search of livelihood. After the Wildlife Protection Act of 1972 and other forest laws became more regressive, the tribes started moving in groups from place to place in search of livelihood. Gradually they started selling forest products including hair oil, honey and spices. Now they are emerging as entrepreneurs selling traditional products including massage oil , hair oil , Hibiscus power , extraction of plant oils , and spices. Some of the members of the tribe are also travelling to African countries where herbal products especially hair oil are in greater demand. Currently , the members of this tribe are claiming that 70 percent of them are cashing in on the sale of Adivasi hair oil trend which has become very popular after celebrity endorsements. from bird catchers to entrepreneurs of traditional forest products the tribe is emerging as one of the culturally significant tribe in Hassan district. But there is a need to study constraints and limitations hampering their prospective socio economic progression.